MATHEMATICAL MODEL OF UNMANNED AERIAL VEHICLES CONTROL - RODINKOV, YURIY; SAVITSKIY, ANTON (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Researchment and examination of the mathematical model for controlling quadcopter-type aerial vehicles. During wartime, the use of unmanned aerial vehicles (UAVs) in agriculture becomes not only a technologically advanced solution but also a vital practice for ensuring safety, enhancing efficiency, and maintaining food stability in the country. The use of UAVs reduces risks to the lives and health of farmers and agricultural workers, as they can remotely control the drones and avoid hazardous zones. UAVs can also fly over areas where there is a risk of mines or other dangerous remnants of war, making them indispensable for monitoring and assessing field conditions. The use of quadcopters can decrease the need for physical labor, reduce fuel and equipment costs, and optimize the use of agrochemicals. Accurate monitoring of field and crop conditions can significantly reduce losses, which is critically important during wartime when resources are limited. Quadcopters equipped with high-resolution cameras and sensors can collect detailed data on soil moisture, crop health, and pest infestations. This data can be processed using advanced algorithms to provide farmers with actionable insights, enabling precise interventions. For instance, targeted spraying of pesticides and fertilizers ensures that only the necessary areas are treated, reducing wastage and minimizing environmental impact. Additionally, the ability to perform frequent and comprehensive surveys of large areas helps in early detection of problems, allowing for timely corrective measures. This proactive approach can lead to better crop yields and quality, essential for food security during wartime. The integration of UAVs in agricultural practices supports sustainable farming by promoting efficient resource use and reducing the dependency on manual labor. In the context of ongoing conflicts, UAVs offer a strategic advantage by facilitating continuous agricultural operations without exposing workers to danger. They can also be used to deliver essential supplies and medical aid to remote or inaccessible areas, further extending their utility beyond traditional agricultural applications. Moreover, the deployment of UAVs for agricultural purposes aligns with global trends towards digitalization and smart farming, positioning the country at the forefront of agricultural innovation. Embracing this technology can pave the way for post-war recovery and modernization of the agricultural sector, ultimately contributing to the country’s resilience and long-term development.